The Impact of Knowledge Management on Competitive Advantage in Private Sector Companies: A Case Study of Al-Hayat Investment Company (The International Journal for Scientific Research, 2024)
This study aimed to demonstrate the impact of knowledge management in achieving competitive advantage in Al-Hayat Investment Company. For the purpose of achieving this, the researcher followed the descriptive analytical approach in its social survey style, where an electronic questionnaire was distributed to a sample of (86) individuals from the company’s employees, and (65) individuals responded. Of them, this percentage constitutes 74%. The “SPSS” Statistical Package for the Social Sciences application was relied upon to perform descriptive and analytical analyzes of the data, after the stability and validity of the study tool was proven through the Cronbach’s alpha reliability coefficient and the Pearson correlation coefficient. The study found a high level of knowledge management and competitive advantage at Al-Hayat Investment Company. The study also found that there is a positive moral effect of knowledge management on the competitive advantage at Al-Hayat Investment Company in general. In detail, the dimension of knowledge generation does not affect competitive advantage similar to the rest of the dimensions of knowledge management that have proven effective in Enhancing competitive advantage. The study also found that there are no statistical differences attributable to the variables of gender and practical qualification, with limited differences attributable to the years of experience variable in favor of the 5 – 10 year group, but these differences are limited to the application of knowledge, and the competitive advantage is lost and there are no statistical differences. Towards the variable of years of experience towards any other dimension. The study concluded with some recommendations, the most important of which are: the need for the company to adopt new methods of shopping, target new markets, and innovate modern promotional methods.
Keywords: Knowledge Management; Competitive Advantage; Private Sector; Investment Companies